The stability of plant richness, composition, and cover responds nonlinearly to warming in a decade‐long experiment - Ruonan Shen; Yangjian Zhang; Juntao Zhu; Yunlong He; Zhoutao Zheng; Guang Zhao; Nan Cong; Bo Zhao; Xianzhou Zhang; Lin Jiang; Yann Hautier (Ecology, 2025)
Global warming is expected to change the diversity, composition, and functioning of plant communities. However, it remains unclear how warming alters the temporal stability of different aspects of plant communities and the extent to which these different aspects are interlinked or respond differently to warming. Here, using data from a 10‐year, multi‐level warming experiment in an alpine grassland, we quantified the temporal stability of three plant community aspects—species richness, composition, and cover—in response to warming scenarios that increase soil temperature by 0.4, 1.6, 2.1, and 2.5°C. We found a nonlinear concave stability response to warming for each of the three community aspects investigated. That is, moderate warming caused moderate increases in the stability of richness, composition, and cover, whereas severe warming caused strong decreases in stability. Additionally, we found that the processes contributing to stability differed among the three community aspects, with warming weakening the relationships between them. Severe warming reduced the stability of cover by reducing the stability of dominant species and species asynchrony. Compositional stability decreased due to declines in species richness, species asynchrony, and dominant species stability. Richness stability decreased due to a decline in species richness. Our results demonstrate that the stability of different community aspects responds nonlinearly to future warming scenarios, with moderate warming stabilizing but high‐level warming destabilizing plant species richness, composition, and cover. Our findings emphasize the collective influence of species richness, species asynchrony, and dominant species stability as key factors modulating community stability in the context of global warming.